Okta Administration : Up and Running : Implement enterprise-grade identity and access management for on-premises and cloud apps /: Up and Running : Implement enterprise-grade identity and access management for on-premises and cloud apps. (2020) - Stjernlof, Lovisa Stenbacken; Vries, HenkJan de
No abstract available